Adipose tissue micrograft in a scaffold of plasma-gel combined with platelet-derived growth factors in dermal wrinkle regeneration - Svolacchia, Fabiano; Svolacchia, Lorenzo (Scripta Medica, 2021)
Background: The dermal aging process and the formation of deep wrinkles are a biological involution that also involves the regeneration system of cells immersed in the extracellular matrix and the papillary dermis. The progressive loss of niches of adult stem cells (MSCs) is more evident after the first third of life; it increases the phenotypic expression and the characteristics of the tissue senescence process. The purpose of this study was to clinically demonstrate that in viable micrograft there may be an improvement of deep wrinkles and surrounding tissues. Methods: This study involved 11 female patients who underwent the correction of deep dermal wrinkles through a suspension containing 0.8 mL of viable micrografts in a 5 mL plasma gel scaffold, obtained from the centrifugation of a 20 cc venous sample peripheral blood, gelled by heat in a dry steriliser and the buffy coat coming from the same venous sample, in order verify overtime the improvement of the interested anatomical area. Individual signs of wrinkles and the degree of correction obtained for each treatment and each area were objectively evaluated by using a 10-0 visual analog scale (VAS), Modified Vancouver scale and Berardesca’s scale. Results: With this technique excellent results were obtained. In fact, wrinkles were improved, as well as surrounding tissues, even after 60 days, as shown by the Berardesca’s, VAS and Modified Vancouver scales. Conclusion: This retrospective clinical evaluation allowed us to consider the excellent clinical results obtained with this method for the treatment of deep wrinkles and surrounding tissues, through a suspension of progenitors with MSCs derived from adipose tissue (ADSCa) in a not inflammatory plasma gel scaffold combined with buffy coat.